Pengaruh Promosi, COD (Cash On Delivery), dan Viral Marketing Terhadap Keputusan Pembelian Market Place Lazada. (Studi Kasus Mahasiswa FEB Universitas Islam Malang) - Lestari, Astri Dewi; Nurhajati, Nurhajati; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract The aim of this research is to find out the "Influence of Promotions, COD (Cash on Delivery), and Viral Marketing on Purchasing Decisions at the Lazada Market Place." The data collection method uses purposive sampling, namely taking samples from the population based on certain criteria. The data analysis technique used to measure the question indicators in the questionnaire is the Likert scale. In this research, the data source used is primary data using analysis tools and statistics from the IMB SPSS25 program. This research uses a data collection method with a questionnaire and the sample used in this research is 80 respondents. Data analysis methods include quantitative analysis using multiple linear regression techniques and partial hypothesis testing (t test). The results of this research show that promotion partially has a positive and significant effect on purchasing decisions at the Lazada market place with a significance level of 0.000 > 0.05, then Cod (Cash on Delivery) partially does not have a positive and significant effect on purchasing decisions at the Lazada market place with a significance level of 0.308 > 0.05 and Viral Marketing partially has a positive and significant effect on Purchasing Decisions at the Lazada Market Place with a significance level of 0.001 < 0.05.  Keywords: Promotion, COD (Cash on Delivery), Viral Marketing, and Purchase Decisions, Marketplace Lazada